1985
DOI: 10.1111/j.1360-0443.1985.tb03012.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Alcohol Consumption in the Netherlands: 1958–1981

Abstract: Summary Between 1958 and 1981 the increase in per capita consumption in the Netherlands was more than 300 per cent. Survey dam of 1958, 1970 and 1981 are used to study changes in mean consumption and in the frequency distribution of consumption of different subpopulations. In most subpopulations the percentage of abstainers did not show significant changes. Differences in mean consumption between subpopulations have generally become larger, especially between 1958 and 1970. All subpopulations with an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
(10 reference statements)
3
11
0
2
Order By: Relevance
“…Binge drinking has been reported to be more of a social behavior, facilitated by the social environment, among men Downloaded by [University of Colorado at Boulder Libraries] at 10:57 20 December 2014 compared to women (Norman et al, 1998). Also, in accordance with other studies among the general Dutch population (Bongers, 1998;Droomers, 1999;Knibbe, Drop, Van Reek, & Saenger, 1985), our study shows a trend indicating higher excessive drinking and problem drinking among less educated people. Educational differences in alcohol use have partly been related to a higher amount of stress experienced among lower educated groups (Droomers, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Binge drinking has been reported to be more of a social behavior, facilitated by the social environment, among men Downloaded by [University of Colorado at Boulder Libraries] at 10:57 20 December 2014 compared to women (Norman et al, 1998). Also, in accordance with other studies among the general Dutch population (Bongers, 1998;Droomers, 1999;Knibbe, Drop, Van Reek, & Saenger, 1985), our study shows a trend indicating higher excessive drinking and problem drinking among less educated people. Educational differences in alcohol use have partly been related to a higher amount of stress experienced among lower educated groups (Droomers, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…This association was also positive across all studies, and is consistent with results reported in individual longitudinal studies (e.g. Clark & Cahalan, 1976;Glynn et al, 1984;Knibbe et al, 1988;Temple & Leino, 1989). The predictive significance of baseline level of education is not uniform (i.e.…”
Section: The Findingssupporting
confidence: 89%
“…The relation between alcohol consumption and education level has been investigated in several studies, which reported that people (both genders) with fewer qualifications are more prone to heavy drinking (Knibbe et al, 1985;Droomers et al, 1999;van Oers et al, 1999).…”
Section: Introductionmentioning
confidence: 99%